Harmful Algal Species in the Tebrau Strait: An SEM Observation of the Dinofl agellate Assemblage - Tan, Toh Hii; Lim, Po Teen; Roziawati, Mohd Razali; Leaw, Chui Pin (National University of Singapore, 2013)
Harmful algal bloom (HAB) is a natural phenomenon due to the increase of algal cell density in the water column that subsequently causes deleterious effects to natural environments as well as mankind. HABs in the country mainly occurred when a particular group of dinofl agellate cells proliferate in the eutrophied semi-enclosed coastal water body. In this study, dinofl agellate species composition in the Tebrau Strait was determined by scanning electron microscope (SEM). Plankton samples were collected by a 20-micron plankton net haul at several locations of the strait. Samples were undergone fi xation, serial dehydration and followed by critical point drying. Samples were then observed under a JEOL analytical SEM. Total of 11 dinofl agellate species were identifi ed, with 7 species known to be associated with HABs events. The occurrence of a fi sh-killing unarmoured dinofl agellate, Karlodinium venefi cum was reported for the fi rst time from Malaysian waters. The presence of this and other potentially harmful dinofl agellate species in the strait should be taken seriously by the respective authorities in future expansion of aquaculture industry in the strait.